2020
DOI: 10.2174/1566524020666191219102746
|View full text |Cite
|
Sign up to set email alerts
|

Depression as is Seen by Molecular Spectroscopy. Phospholipid- Protein Balance in Affective Disorders and Dementia

Abstract: There is an expanding field of research investigating the instrumental methods to measure the development of affective disorders. The goal of the commentary is to turn the attention of medical practitioners at the molecular spectroscopy techniques (FTIR, Raman and UV-Vis) that can be applied for monitoring and quantification of the phospholipid-protein balance in human blood serum of depressed patients. Even facial overview of cited original research strongly suggests that dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Previous studies have indicated that there are close associations between neuropsychiatric disorders and metabolism, including mitochondrial energy metabolism [ 50 ], glucose metabolism [ 51 ] and amino acid metabolism [ 52 ]. These studies have also found that phospholipids and proteins [ 53 , 54 ], cortisol levels [ 55 ] or vitamins [ 56 , 57 ] in blood serum can be used as potential diagnostic biomarkers in neuropsychiatric disorders. The abnormal changes of these substances may be linked to symptoms of psychiatric disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that there are close associations between neuropsychiatric disorders and metabolism, including mitochondrial energy metabolism [ 50 ], glucose metabolism [ 51 ] and amino acid metabolism [ 52 ]. These studies have also found that phospholipids and proteins [ 53 , 54 ], cortisol levels [ 55 ] or vitamins [ 56 , 57 ] in blood serum can be used as potential diagnostic biomarkers in neuropsychiatric disorders. The abnormal changes of these substances may be linked to symptoms of psychiatric disorders.…”
Section: Methodsmentioning
confidence: 99%